ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KECELAKAAN KERJA DI PT INDO COCO PRIMA LESTARI LABUHAN BATU UTARA SUMATERA UTARA TAHUN 2023 - Sihotang, Dewi Sartika (Jurnal Inovasi Kesehatan Masyarakat, 2023)
The implementation of the occupational safety and health management system consists of various programs to protect and improve the welfare of workers. PT Indo Coco Prima Lestari currently employs 115 employees. Commodity materials produced are mostly for export. The need for production materials per day is 80 tons of coconut to produce 6 tons of coconut essence and core which is formed into granules. The high production process is in line with the high risk of work accidents that can be experienced by workers. Analyzing Factors Associated with Work Accidents at PT. Indo Coco Prima Lestari, Labuhan Batu Utara, North Sumatra in 2023. The type of research used is quantitative research using a cross-sectional approach or research that aims to analyze factors related to work accidents. There were 110 research respondents. Years of Service, Knowledge, Attitudes, Actions and K3 Training related to Occupational Accidents, but the most dominant is the variable of Working Period which has a 3.199 chance of causing Work Accidents. Working period is directly related to work experience, the longer a person's working period, the higher the experience and flight hours of the workers, so that workers will better understand how to work safely so that work accidents do not occur. Knowledge, Attitudes, Actions and K3 Training related to Occupational Accidents, but the most dominant is the variable of Working Period seen based on the RP value on the Multivariate test results it is known that Working Period has the greatest value of 3.199 (0.577-17.731) so it can be concluded that Working Period has a 3.199 chance of causing Work Accidents. Company management needs to improve the comfort of workers so that the flow of workers in and out can be maintained properly, for example by making long work contracts, conducting regular training for employees and making teamwork also improve work time, can also improve worker skills in carrying out company productivity. PT. Indo Coco Prima Lestari, Labuhan Batu Utara, North Sumatra in 2023 needs to reconsider termination of employment or entering into long term work contracts so that workers become more experienced in their field of work.